FACTORS ANALYSIS OF GRAMMAR ERRORS IN STUDENTS’ WRITING: A BASIS FOR NEW TEACHING METHODS - Erna Dwinata; Umdatul Khoirot (STKIP PGRI Tulungagung, 2019)
Meaning cannot be transfered well if there is errorin grammar. This paper aims to determine the grammar errors committed by the 6th semester students of English Education Department as basis for new method. Specifically, the study aims to answer: 1) what grammar errors are committed by the 6th semester students of English Education in their written text; and 2) what factors caused the students to commit these errors in writing as evident on their written composition. The respondents of this study consisted of english education students, Semester 6. Result showed that the common grammar errors committed by the 6th semester students of English Education are: verb f, tenses of the verb, sentence structure and word order, the use of articles and preposition, punctuation and capitalization, and spelling. 2 Big factors as the cause of errors are : direct factors and indirect factors.